Outer Membrane Vesicles Prime and Activate Macrophage Inflammasomes and Cytokine Secretion In Vitro and In Vivo - Cecil, Jessica D.; O’Brien-Simpson, Neil M.; Lenzo, Jason C.; Holden, James A.; Singleton, William; Perez-Gonzalez, Alexis; Mansell, Ashley; Reynolds, Eric C. (Frontiers in Immunology, 2017)
Outer membrane vesicles (OMVs) are proteoliposomes blebbed from the surface of Gram-negative bacteria. Chronic periodontitis is associated with an increase in subgingival plaque of Gram-negative bacteria, Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia. In this study, we investigated the immune-modulatory effects of P. gingivalis, T. denticola and T. forsythia OMVs on monocytes and differentiated macrophages. All of the bacterial OMVs bound and were phagocytosed by monocytes, M(naïve) and M(IFNγ) macrophages at different ratios, as well as induced NFκB activation and increased TNFα, IL-8 and IL-1β cytokine secretion. P. gingivalis OMVs were also found to induce anti-inflammatory IL-10 secretion. Although unprimed monocytes and macrophages were resistant to OMV-induced cell death, LPS or OMV priming resulted in a significantly reduced cell viability. P. gingivalis, T. denticola and T. forsythia OMVs all activated inflammasome complexes, as monitored by IL-1β secretion and ASC speck formation. ASC was critical for OMV-induced inflammasome formation, while AIM2-/- and Caspase-1-/- cells had significantly reduced inflammasome formation and NLRP3-/- cells exhibited a slight reduction. OMVs were also found to provide both priming and activation of the inflammasome complex. High resolution microscopy and flow cytometry showed that P. gingivalis OMVs primed and activated macrophage inflammasomes in vivo with 80% of macrophages exhibiting inflammasome complex formation. In conclusion, periodontal pathogen OMVs were found to have significant immunomodulatory effects upon monocytes and macrophages and should therefore influence pro-inflammatory host responses associated with disease.